2008
DOI: 10.1111/j.1365-2656.2008.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Lazy males? Bioenergetic differences in energy acquisition and metabolism help to explain sexual size dimorphism in percids

Abstract: Summary1. Differences in energy use between genders is a probable mechanism underlying sexual size dimorphism (SSD), but testing this hypothesis in the field has proven difficult. We evaluated this mechanism as an explanation for SSD in two North American percid species -walleye Sander vitreus and yellow perch Perca flavescens . 2. Data from 47 walleye and 67 yellow perch populations indicated that SSD is associated with the onset of maturation: typically, males of both species matured smaller and earlier and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 61 publications
9
103
1
Order By: Relevance
“…However, males can also have additional 'reproduction-related' costs, namely territorial behaviour or parental care, which should be accounted. Differences in energy acquisition and assimilation seem to be the underlying cause for sexual differences in some flatfishes like dab L. limanda (Lozán 1992) and in percids (Rennie et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, males can also have additional 'reproduction-related' costs, namely territorial behaviour or parental care, which should be accounted. Differences in energy acquisition and assimilation seem to be the underlying cause for sexual differences in some flatfishes like dab L. limanda (Lozán 1992) and in percids (Rennie et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…McClain et al 2006 observed similar patterns in male and female walleye growth and Hg concentrations and alluded to Henderson et al 2003 to explain these findings. Rennie et al 2008 suggested that differences in male and female walleye growth and Hg concentrations were likely attributable to ''laziness'', suggesting that male walleye foraging was greatly reduced at the onset of maturity presumably to avoid predation as posited by Roff 1983, though the authors did not discount the importance of the supposition by Henderson et al 2003. Our results indicate that another mechanism may be influencing walleye sexual dimorphism and Hg concentrations.…”
Section: Discussionmentioning
confidence: 66%
“…For example, fish sex (Henderson et al 2003;Rennie et al 2008), size (Harris and Bodaly 1998), diet and trophic position (Harris and Bodaly 1998;Power et al 2002;Sackett et al 2010) and growth (Simoneau et al 2005;Ward et al 2010) have all been shown to play a role in Hg bioaccumulation. Anthropogenic manipulation of food webs can alter the dynamics of these factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if 321 there are additional sex-specific differences in consumption, assimilation, metabolism or 322 mortality, the optimal growth trajectories of males and females may diverge earlier in life, 323 and before final structural size is attained. When such differences are caused by differences in 324 behavior between males and females (e.g., Rennie et al, 2008), the model may be extended 325 to include reversible behavioral transitions (which can then be optimized separately for males 326 and females), in addition to the irreversible structural growth, as presented and discussed in 327…”
Section: Such Losses Of Reserves Mass (And Thus Instantaneous Total Bmentioning
confidence: 99%